Réponses

2014-06-17T21:43:37+02:00
4x+1=-9
4x = -10
x = -5/2

-6x-1=3x-5
-1+5 = 3x+6x
4=9x
x=4/9
x=2/3

7x-(2x+5)=2
7x-2x-5=2
5x = 7
x = 7/5

B=(6-b)(8b-1)
=48b-6-8b²+b
= -8b² + 49b - 6

c=(3a+2)(5a-3)
= 15a²-9a+10a-6
= 15a² + a - 6

D=(9c+2)(-4b-3)

= -36bc - 27c - 8b - 6
2014-06-17T21:48:22+02:00
4x + 1 = - 9
4x = - 9 - 1
4x = - 10
x = -10/4
x = - 2,5

-6x - 1 = 3x - 5
- 6x - 3x = - 5 + 1
- 9x = - 4
x = 4/9

7x - (2x + 5) = 2
7x - 2x - 5 = 2
7x - 2x = 2 + 5
5x = 3
x = 3/5
x = 0,6

B = (6 - b) (8b - 1)
B = 48b - 6 - 8b² + b
B = - 8b² + 49b - 6

c = (3a + 2) (5a - 3)
c = 15a² - 9a + 10a - 6
c = 15a² + a - 6

D = (9c + 2) (-4b - 3)
D = - 36bc - 27c - 8b - 6

bonjour, pour la 3eme équation une petite erreur s'est glissée dans votre calcul j'ai l'impression (5 + 2 = 7) ;-)